Does SOFR-linked debt cost borrowers more than LIBOR-linked debt? - Sven Klingler; Olav Syrstad (Norges Bank, 2023)
We investigate if the benchmark transition from London Interbank Offered Rate (Libor) to Secured Overnight Financing Rate (SOFR) affects the costs of borrowing floating rate debt. The primary market for dollar-denominated floating rate notes (FRNs) provides an ideal laboratory to study these e ects. Comparing the spreads of FRNs linked to LIBOR and SOFR, issued by the same entity during the same month, we find a significantly lower yield spread for SOFR-linked debt after adjusting for the maturity-matched spreads from the swap market. In addition, despite identification challenges, we observe a quantitatively similar pattern in the syndicated loan market.
hdl:11250/3073368
Keywords: E43; G12; G18; G29; 330; Benchmark rates; floating rates; financial regulation; LIBOR; SOFR